2007
DOI: 10.1007/s00464-006-9140-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of robotic assistance on the “learning curve” for laparoscopic hand-assisted donor nephrectomy

Abstract: Specific changes in operative technique over time have improved patient safety and diminished complications with RHADN. Currently, RHADN can be performed expeditiously with a minimal rate of complications and conversion to open procedure by a surgical team with appropriate training and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 28 publications
(34 reference statements)
7
54
1
6
Order By: Relevance
“…The authors reported that hand-assisted RALDN increased the safety of the operation by allowing rapid control of catastrophic bleeding and avoiding excessive manipulation of the kidney during extraction [9]. This report on 214 RALDN patients (2007) [10] remains the largest cohort study, and provides insight into the learning curve involved in mastering robotic-assisted transplant surgery. Notably, Horgan et al [10] [8].…”
Section: Discussionmentioning
confidence: 89%
“…The authors reported that hand-assisted RALDN increased the safety of the operation by allowing rapid control of catastrophic bleeding and avoiding excessive manipulation of the kidney during extraction [9]. This report on 214 RALDN patients (2007) [10] remains the largest cohort study, and provides insight into the learning curve involved in mastering robotic-assisted transplant surgery. Notably, Horgan et al [10] [8].…”
Section: Discussionmentioning
confidence: 89%
“…The largest study published by Horgan et al [17] including 250 living kidney donors shows that the mean operative time was strongly reduced with an increasing number of RADNs performed. Janki et al [9] showed a significant improvement in total operative time after 60 RADNs performed, indicating the importance of the learning curve in RADN.…”
Section: Resultsmentioning
confidence: 99%
“…This has led to the implementation of robotic-assisted donor nephrectomy (RADN) in some centers [17]. The first series of 12 successful RADN were performed with daVSS [17].…”
Section: Live Kidney Donationmentioning
confidence: 99%
“…Diese Operation setzt ebenfalls laparoskopisches Geschick voraus und ist mit einem signifikanten Lernkurveneffekt vergesellschaftet [17,18]. Durch Roboterunterstüt-zung berichteten Horogan et al [19] von warmen Ischämiezeiten von <2 min und einer Graft-Überlebensrate von 98%. Diese positiven Ergebnisse konnten auch bei Vorliegen von Gefäßanomalien erreicht werden.…”
Section: » Die Technischen Vorteile Vonunclassified